Assessing the Challenges of Marriage Breakdown in Families Among the Christians of St. Paul Besania Church in Central Buganda Diocese - Emmanuel Muwanguzi (Uganda Christian University, 2024)
The study was carried out in St Paul Besania Church, Mbaale Mpigi Archdeaconry. Main purpose of the study was to identify marriage breakdown as an outstanding challenge in families of Christians of St. Paul Besania. The researcher also wanted to know more about the view of the public on marriage breakdown which has been rampant today especially due to unemployment and poverty in very many families. The study also considered using both qualitative. Data was collected through personal interviews using a structured questionnaire which include 50 respondents who helped in improving the primary data. In depth interviews were held with parents who have faced the problem of marriage breakdown in families. Questionnaires administered to respondents were verified edited and coded. Row frequencies were generated to produced descriptive data. However, because of limited time the researcher was not able to use bigger sample size, its therefore recommended that future researcher should use larger sample size so as to come up with a better analysis of impact of marriage breakdown in St. Paul Besania Church. There are still some weaknesses in enforcement of laws concerning marriage breakdowns therefore, there is need to strengthen legislation framework that will help in dealing in marriage breakdown cases.
Undergraduate Research